Biomass steam gasification for hydrogen production: A systematic review - Inayat, A. (Springer International Publishing, 2014)
The production of hydrogen as a clean and sustainable fuel is becoming attractive due to the energy crisis and increasing environmental issues associated with fossil fuel usage. Biomass steam gasification with in situ carbon dioxide capture has good prospects for the production of hydrogen-rich gas. Furthermore, hydrogen yield can be enhanced using catalyst steam gasification. This chapter comprises the literature review on both the approaches, i.e., experimental and modeling used to study the hydrogen production from biomass gasification specifically using pure steam as gasification agent. There were several modeling approaches for gasification process based on the kinetics, equilibrium, and the fluid dynamics behaviors. A detailed discussion has been carried out in this chapter on modeling and simulation for hydrogen production from biomass based on kinetics modeling. Experimental studies have been published on steam gasification and steam gasification with CO2 capture and catalytic steam gasification has been discussed. Gasification for hydrogen production from oil palm empty fruit bunch has also been discussed. Â© 2014 Springer International Publishing Switzerland. All rights reserved.